The limitations of QALY: a literature review - Pettitt, D; Raza, S; Naughton, B; Roscoe, A; Ramakrishnan, A; Ali, A; Davies, B; Dopson, S; Hollander, G; Smith, J; Brindley, D (OMICS International, 2016)
Introduction: The Quality Adjusted Life Year (QALY) is a recognised metric used to evaluate new and innovative healthcare treatments and optimise resource allocation via rational and explicit methodologies. This review examines present limitations of the QALY metric and foreseeable challenges linked to the advancement of regenerative medicine. Methods: The extant literature was reviewed through electronic searches of four key databases; namely Medline, EMBASE, Econlit and Cochrane. Manuscripts were selected according to pre-determined inclusion criteria.